2013
DOI: 10.1109/tpds.2012.324
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Analysis of an Internet Streaming Service to Mobile Devices

Abstract: Abstract-ReceivingInternet streaming services on various mobile devices is getting increasingly popular, and cloud platforms have also been gradually employed for delivering streaming services to mobile devices. While a number of studies have been conducted at the client side to understand and characterize Internet mobile streaming delivery, little is known about the server side, particularly for the recent cloud-based Internet mobile streaming delivery. In this work, we aim to investigate the Internet mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…We analyze the performance of the system when the p i 's satisfy the Zipf distribution which is defined as follows: the fraction of requests for the i th most popular content is proportional to i −β , where β ≥ 0 is a constant, known as the Zipf parameter. This is motivated by the fact that empirical studies of many VoD services have shown that the content popularity distributions match well with the Zipf distribution [18]- [21]. Typical values of β lie between 0.6 and 2.…”
Section: B Request Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyze the performance of the system when the p i 's satisfy the Zipf distribution which is defined as follows: the fraction of requests for the i th most popular content is proportional to i −β , where β ≥ 0 is a constant, known as the Zipf parameter. This is motivated by the fact that empirical studies of many VoD services have shown that the content popularity distributions match well with the Zipf distribution [18]- [21]. Typical values of β lie between 0.6 and 2.…”
Section: B Request Modelmentioning
confidence: 99%
“…In Figure 13, we plot the mean transmission rate for the KS+MLP policy and the lower bound on the expected transmission rate as a function of the Zipf parameter β. Typical values of β for video of demand systems lie between 0.6 and 2 [18]- [21]. We simulate a system with 1000 contents (n = 1000) and 200 caches (m = 200) for two different values of storage per cache.…”
Section: Next We Compare the Performance Of The Knapsack Storage + Mmentioning
confidence: 99%
“…The proliferation of mobile devices is characterised by substantial heterogeneity, i.e., a recent analysis of an Internet mobile streaming service reported "3,400 hardware models with 109 screen resolutions running 14 mobile OS, 3 audio codecs and 4 video codecs" [24]. Obviously the format of the content may be inadequate for certain devices (e.g., incompatible codecs, very low resolution) and/or it may waste network resources (e.g., streaming high resolution video to low resolution devices).…”
Section: Exposed Information a From Content Identifiers To Contmentioning
confidence: 99%
“…Mobile devices are a necessity for people's daily life, especially since the explosion of smart phone and tablet [1]. With the fast development of wireless technologies [2,3] and wide deployment of 3G/4G/LTE base stations and WiFi hotspots [4,5], the mobile devices can be connected to the Internet at anytime and at anywhere [6], where the communication among peers becomes more convenient.…”
Section: Introductionmentioning
confidence: 99%